The magnitude of anemia and associated factors among pregnant women attending public institutions of Shire Town, Shire, Tigray, Northern Ethiopia, 2018 - Awoke Kebede; Hadgu Gerensea; Freweyni Amare; Yared Tesfay; Girmay Teklay (BMC Research Notes, 2018)
Abstract Objective Anemia is a widespread health problem among pregnant women causing maternal/infant morbidity and mortality mainly in low-income countries. Understanding of the magnitude of anemia and related socio-demographic variables in a specific setting would help scale-up preventive and therapeutic measures in a locality. So that this study focuses on the magnitude of anemia and its associated factor among pregnant women attending antenatal care in public hospitals of shire town and using institution based cross-sectional study design on 480 randomly selected study subjects. Result The overall prevalence of anemia was 16.3%. Majority of the participants (52%) have mild anemia (10–10.9 gm/dl). Pregnant mothers with human immunodeficiency virus, intestinal parasitic infection and having lower inter-pregnancy gap were significant predictors of anemia. Preventing infection of the mother during pregnancy and making the gap between pregnancies are necessary.